Isolation And Identification of Cyanobacteria from Selected Caves of Bulabog Putian National Park Dingle, Iloilo, Western Visayas, Philippines - Mary Lou Crucero Arabaca; Noel D. Roble; Jenelle Mae B. Sanchez (Journal of Tropical Life Science, 2022)
Cyanobacteria are photosynthetic, gram negative, and diverse group of prokaryotic organisms, inhabiting a wide range of habitats including caves. This study was aimed to isolate and identify cyanobacteria in selected caves of Bulabog Putian National Park, Dingle, Iloilo, Western Visayas, Philippines. Based on morphology and 16S rRNA gene sequence analysis six strains of cyanobacteria were identified. The sequence homology search by BLAST program revealed that the closest relative of the six strains was Leptolyngbya sp. (similarity - 94.62 Calothrix sp. (similarity – 97.07%), Chroococcidiopsis cubana (similarity – 99.21%), Onodrimia javanensis (similarity – 96.27%), Chroakolemma pellucida (similarity – 94.74%), and Albertania skiophila (similarity – 98.40%), belonging to Order Chroococcidiopsales, Nostocales, and Synechococcales. The phylogenetic tree revealed the taxonomic positions of the six cyanobacterial strains. Based on the results, six newly identified strains of cyanobacteria have been discovered from the caves of Bulabog Putian National Park. Further studies such as the polyphasic approach and other taxonomic characterizations are needed for the description of these new novel taxa of cyanobacteria.